ХРАНЕНИЕ ПРОМЫШЛЕННЫХ ШТАММОВ ВИННЫХ ДРОЖЖЕЙ (Experimental biology, 2015)
The article basic chemical indicators of apple-based used in wine production. This kind of substsnces are generated from yeast flora of Almaty fruit-berry gardens. The results of the research suggest to use the following sorts of apple-based substances for wine production in Kazakрstan: apple 2(2) and aport 199.
Keywords: apple-based; aport